Teflon Injection into the Trachea Causes Predictable Fibroblastic Response and Collagen Deposition: A Pilot Study. Issue 4 (October 2016) - Longoria, Javier A.; Fujiwara, Miwa; Guerra, Catalina; Lee, Jeffrey L.; Sassoon, Catherine S.H.; Mazdisnian, Farhad
Abstract : Background: Expiratory central airway collapse is an increasingly recognized abnormality of the central airways and may be present in as many as 22% of patients evaluated for chronic obstructive pulmonary disease and/or asthma. Many current treatment options require invasive procedures that have been shown to cause significant morbidity and mortality. To test the hypothesis that Teflon injection will induce sufficient fibroblast proliferation and collagen deposition, we evaluated the time course on the effect of Teflon injection in the posterior membranous trachea on the histopathology of the tracheobronchial tree. Methods: Six Yucatan Pigs were assigned to undergo general anesthesia and injection of 0.3 to 0.5 mL of sterile Teflon paste in 50% glycerin into the posterior membranous tracheal wall. A control pig received an equivalent volume of glycerin. Animals were euthanized in predefined intervals and tracheas were excised and examined under light microscopy for identifying fibroblast proliferation and collagen deposition. Results: Compared with the control pig, the Teflon injection site showed tissue reaction of fibrohistiocytic proliferation and subsequent collagen deposition in all animals. Furthermore, the increased fibroblast proliferation and collagen deposition were time dependent ( P <0.01). Conclusion: This pilot study demonstrates histopathologic changes in the trachea after Teflon injection, comprised of increased fibroblast activity and collagen deposition that could be of potential use in creating greater airway rigidity in patients with sever diffuse excessive dynamic airway collapse.